THE EFFECT OF DECOLLEMENT DIP ON GEOMETRY AND KINEMATICS OF MODEL ACCRETIONARY WEDGES - Koyi H.A.; Vendeville B.C. (My University, 2003)
We conducted a series of sand-box models shortened asymmetrically above a frictional-plastic decollement to study the influence of amount and sense of the decollement dip on the geometry and kinematics of accretionary wedges. Model results illustrate that the amount and direction of decollement dip strongly influence the geometry and mode of deformation of the resulting wedge. In general, for models having similar decollement frictional parameters, the resulting wedge is steeper, grows higher and is shorter when shortened above a decollement that dips toward the hinterland. At 42% bulk shortening, the length/height ratio of wedges formed above a 5°-dipping decollement was equal to 2.4 whereas this ratio was equal to 3 for wedges shortened above a horizontal decollement. Moreover, models with a hinterland dipping decollement undergo larger amounts of layer parallel compaction (LPC) and area loss than models shortened above a non-dipping decollement. The effect of decollement dip on wedge deformation is most pronounced when basal friction is relatively high (μb=0.55), whereas its effect is less significant in models where the basal decollement has a lower friction (μb=0.37). Model results also show that increasing basal slope has a similar effect to that of increasing basal friction; the wedge grows taller and its critical taper steepens.
Keywords: ACCRETIONARY WEDGES; SANDBOX MODELS; DECOLLEMENT DIP; BASAL FRICTION